Inisiasi Posyandu Remaja Sebagai Upaya Peningkatan Derajat Kesehatan Di Kelurahan Bandarharjo, Semarang - Yuniastuti A; Nugrahaningsih WH Nugrahaningsih WH; R Susanti; Noor AH; Siti A; Budi A; Nur KD; Fitri AS; Nirmala AF; Nabila AL; Agnes DS Agnes DS (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2022)
Bandarharjo is one of the urban villages in the city of Semarang with health problems in adolescents which are quite complex and require comprehensive and integrated treatment that involves all elements from across programs and related sectors. Limited health information, low knowledge of healthy life skills for reproductive health, and limited health infrastructure for adolescents are factors in the low level of health. This needs to be improved through counseling, training, mentoring, and the establishment of a youth posyandu. This community service was carried out in Bandarharjo Village, North Semarang, Semarang City for 8 months. The service method is implemented in four stages, namely preparation, socialization, implementation, and monitoring and evaluation. The initiation of youth posyandu as an effort to improve health status has resulted in the implementation of administrative restructuring training for youth posyandu with youth from Bandarharjo Village as administrators. With the implementation of the youth posyandu initiation program, an increase in the knowledge and skills of adolescents in terms of personal health and environmental health has also been achieved. The activities of the youth posyandu need to be maintained so that they exist and are useful for improving adolescent health.